2022
DOI: 10.1080/13880209.2021.2025255
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical profiles, antioxidation, inhibition of skin extracellular matrix degradation, and anti-tyrosinase activity between mycelium and fruiting body of Cordyceps militaris and Isaria tenuipes

Abstract: Context Cordyceps militaris and Isaria tenuipes (Cordycipitaceae) are high-value fungi that are used for health-promoting food supplements. Since laboratory cultivation has begun for these fungi, increased output has been achieved. Objective This study compared the chemical profiles, antioxidant, anti-tyrosinase, and skin extracellular matrix degradation inhibition between mycelium and fruiting body of C. militaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…A study concerning the effects of Trifolium repens stem and leaf extracts on Chinese cabbage and Viola yedoensis Makino seedlings found that SOD activity showed a decreasing trend with increasing extract concentration ( Zhang and Zhang, 2011 ), which differs from our results that showed SOD activity being promoted at low extract concentrations but inhibited at high concentrations. The decrease in SOD activity in the tissues of sugarcane seedlings may gradually enhance the inhibition of their growth, which may be one of the mechanisms by which seedling antioxidant enzymes adapt to allelopathic stress ( Prommaban et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study concerning the effects of Trifolium repens stem and leaf extracts on Chinese cabbage and Viola yedoensis Makino seedlings found that SOD activity showed a decreasing trend with increasing extract concentration ( Zhang and Zhang, 2011 ), which differs from our results that showed SOD activity being promoted at low extract concentrations but inhibited at high concentrations. The decrease in SOD activity in the tissues of sugarcane seedlings may gradually enhance the inhibition of their growth, which may be one of the mechanisms by which seedling antioxidant enzymes adapt to allelopathic stress ( Prommaban et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fe 2+ can be oxidized to Fe 3+ by lipid peroxides, and Fe 3+ will combine with the thiocyanate to form colored complexes with maximum absorption at 485 nm. LPO can be quantified by calculating the amount of oxidized iron (II) (Prommaban et al, 2022). LOOH+Fe2+LnormalO+Fe3+ ${\rm{L}}\text{OOH}+{\text{Fe}}^{2+}\to {\rm{L}}{{\rm{O}}}^{\bullet }+{\text{Fe}}^{3+}$ LnormalO+Fe2++normalH+LOH+Fe3+ ${\rm{L}}{{\rm{O}}}^{\bullet }+{\text{Fe}}^{2+}+{{\rm{H}}}^{+}\to \text{LOH}+{\text{Fe}}^{3+}$ Fe3++3SCnormalNFe(SCN)3 ${\text{Fe}}^{3+}+3\text{SC}{{\rm{N}}}^{-}\to \text{Fe}{(\text{SCN})}_{3}$…”
Section: Determination Methodsmentioning
confidence: 99%
“…Fe 2+ can be oxidized to Fe 3+ by lipid peroxides, and Fe 3+ will combine with the thiocyanate to form colored complexes with maximum absorption at 485 nm. LPO can be quantified by calculating the amount of oxidized iron (II) (Prommaban et al, 2022).…”
Section: Thiocyanate Methodsmentioning
confidence: 99%
“…The antioxidant potential of JMBF extracted by UAE was evaluated via multiple in vitro tests as described previously, including the scavenging assays of DPPH, ABTS, and hydroxyl radical [ 44 , 45 , 46 ]. Vc was introduced as a positive control substance.…”
Section: Methodsmentioning
confidence: 99%